Whether HER2-positive non-breast cancers are candidates for treatment with Ado-trastuzumab emtansine? - Moghaddas, Azadeh (J Res Pharm Pract, 2016)
The National Comprehensive Cancer Network (NCCN) has recommended Ado-trastuzumab emtansine (T-DM1) as a preferred agent for patients with human epidermal growth factor receptor-2 (HER2)-positive metastatic breast cancer and prior trastuzumab therapy. Overexpression of HER2 was reported in other cancer types such as bladder, gastric and urogenital carcinosarcomas similar to what is discovered in breast cancer. Some preclinical studies demonstrated the potential anti-tumor effects of T-DM1 in HER2-positive non-breast cancers. There is a paucity of data over the clinical evaluation of T-DM1 in human studies of non-breast cancer patients. We review some preclinical and ongoing clinical studies that assessed the efficacy of T-DM1 administration in the treatment of non-breast HER2 positive malignancies. Performing large and well-designed trials in this area is matter of interest and highly recommended.